The Longitudinal Relationship Between Close Friendship and Subjective Well-Being: The Chain Mediation Model of Interpersonal Trust and Perceived Social Support - Runqing Li; Wenhu Xu; Hongyu Nie; Weida Zhang (Behavioral Sciences)
Adolescence is a critical period for developing interpersonal relationships and plays a significant role in the growth of subjective well-being. Establishing positive friendships is one of the most important predictors of subjective well-being. This study employs a longitudinal method, tracking Chinese adolescents to investigate the impact of individuals’ number of close friends on subjective well-being by examining the chain mediating roles of interpersonal trust and perceived social support. Data were collected from 987 junior high school students across five schools in Shandong Province and analysed using SPSS 27.0. The results indicate that the number of close friends at Time 1 (T1) significantly positively affects the level of subjective well-being at Time 3 (T3). At Time 2 (T2), perceived social support mediates the relationship between the number of close friends at T1 and subjective well-being at T3. Furthermore, the number of close friends at T1 has a longitudinal mediating effect on subjective well-being at T3. This effect is mediated by interpersonal trust and perceived social support at T2. This study reveals the mechanisms by which the number of close friends influences subjective well-being among Chinese adolescents. The findings highlight the significance of fostering healthy interpersonal relationships among adolescents in China. This can be achieved by promoting initiatives that enhance levels of interpersonal trust and perceived social support within communities, thereby improving overall subjective well-being among adolescents